2012
DOI: 10.1016/j.surfcoat.2012.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Reactive magnetron sputtering of uniform yttria-stabilized zirconia coatings in an industrial setup

Abstract: Yttria-stabilized zirconia (YSZ) thin films were deposited by reactive magnetron sputtering in an industrial scale setup on silicon wafers as well as commercial NiO-YSZ fuel cell anodes.The texture, morphology, and composition of the deposited films were investigated as a function of deposition parameters. Homogeneous coatings could be deposited over large areas within the coating zone, which is important for industrial applications. The use of substrate bias during film growth was identified as a key paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…YSZ is also used as implant material due to its toughness and biocompatibility [28]. For its ionic conductance, the cubic fluoride form is used as electrolyte in solid-oxide fuel cells [29][30][31][32][33] and as material with reversible oxygen storage capacity when alloyed with CeO 2 [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…YSZ is also used as implant material due to its toughness and biocompatibility [28]. For its ionic conductance, the cubic fluoride form is used as electrolyte in solid-oxide fuel cells [29][30][31][32][33] and as material with reversible oxygen storage capacity when alloyed with CeO 2 [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, S?nderby et al [36] demonstrated the possibility of forming YSZ electrolytes with a thickness on NiO/YSZ anodes of (13 × 13) cm 2 area. However, a whole fuel cell was not produced and studied in this work.…”
Section: Scaling Of the Technology Of Magnetron Deposition Of Ysz Elementioning
confidence: 91%
“…Manufacturing process of the electrolyte The possibility of formation of 2µm -thick YSZ electrolytes on NiO/YSZ anodes with an area of (13 × 13) cm 2 was first shown in [36]. The substrate temperature during the sputtering process was maintained at 500 o C .…”
Section: Magnetron Sputtering Of Ysz Electrolyte Effect Of Depositiomentioning
confidence: 99%
“…However, it has previously been shown that ion bombardment promotes <111> or <220> texture or a mixture thereof as planes in all other directions have higher etch rates and are successfully eliminated by the shadowing process during the growth of the columns [30]. It should be noted that for films deposited on NiO-YSZ substrates an overall texturing is not to be expected as YSZ films previously have been seen to grow epitaxial on the individual grains in the substrate [31]. Therefore, films grown on the two different substrates are not directly comparable.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%